ANALISIS DAYA DUKUNG EKOWISATA BUKIT DOA MAHAWU TOMOHON DI KECAMATAN TOMOHON UTARA KOTA TOMOHON - Ria Brigitta Putri Sumaraw; Gene H. M. Kapantow; Sherly G. Jocom (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2019)
The objective of this research is to analyze carrying capacity of the Bukit Doa Mahawu Tomohon, Tomohon City. This research was conducted for three months from September 2018 to November 2018 which began from preparation to preparation of research reports. Data collection includes pri- mary data and secondary data. Primary data collected through direct measurement techniques using Google Earth calculates the area of land used for tourism. Whereas for secondary data is done through literature studies and collection of library information related to the assessment of carrying capacity of the tourism environment in Bukit Doa Mahawu Tomohon, among others, obtained from the management of Tomohon Hill Doa attractions.Te research result show that the assessment of tourist capacity in Bukit Doa Mahawu, Tomo- hon, results in 13,340 visitors / day physical carryinging capacity (PCC), 11,540 visitors / day and the value of power carrying capacity. effective carrying capacity (Effective Carrying Cappacity / ECC) of 8,655 visitors / day. The current number of visitors to Bukit Doa Mahawu Tomohon tour- ism object is an average of 364 visitors / day. Of the three capacity analyzes that have been carried out, the number of visits currently is still far below the effective number of the capacity of the Bukit Doa Mahawu Tomohon tourism object..Keywords: Ecotourism Carrying Capacity, Bukit Doa Mahawu Tomohon, Tomohon City